De novo microdeletion of BCL11A is associated with severe speech sound disorder. Issue 8 (8th May 2014) - Peter, Beate; Matsushita, Mark; Oda, Kaori; Raskind, Wendy
<x xml:space="preserve">Abstract</x> In 10 cases of 2p15p16.1 microdeletions reported worldwide to date, shared phenotypes included growth retardation, craniofacial and skeletal dysmorphic traits, internal organ defects, intellectual disability, nonverbal or low verbal status, abnormal muscle tone, and gross motor delays. The size of the deletions ranged from 0.3 to 5.7 Mb, where the smallest deletion involved the BCL11A, PAPOLG, and REL genes. Here we report on an 11‐year‐old male with a heterozygous de novo 0.2 Mb deletion containing a single gene, BCL11A, and a phenotype characterized by childhood apraxia of speech and dysarthria in the presence of general oral and gross motor dyspraxia and hypotonia as well as expressive language and mild intellectual delays. BCL11A is situated within the dyslexia susceptibility candidate region 3 (DYX3) candidate region on chromosome 2. The present case is the first to involve a single gene within the microdeletion region and a phenotype restricted to a subset of the traits observed in other cases with more extensive deletions. © 2014 Wiley Periodicals, Inc.